2014
DOI: 10.1155/2014/807347
|View full text |Cite
|
Sign up to set email alerts
|

Improving Learning Performance with Happiness by Interactive Scenarios

Abstract: Recently, digital learning has attracted a lot of researchers to improve the problems of learning carelessness, low learning ability, lack of concentration, and difficulties in comprehending the logic of math. In this study, a digital learning system based on Kinect somatosensory system is proposed to make children and teenagers happily learn in the course of the games and improve the learning performance. We propose two interactive geometry and puzzle games. The proposed somatosensory games can make learners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Even though the results showed that the iPhone method achieved higher knowledge results than the traditional classroom lesson, no statistically significant differences were found between the iPhone and the classroom lesson. Chuang et al (Chuang et al, 2014) studied how happiness can improve learning performance by using interactive systems. The proposed system was a somatosensory system, which is a system that is made up of a number of different receptors like thermoreceptors, photoreceptors, mechanoreceptors, or chemoreceptors like the human body.…”
Section: Related Workmentioning
confidence: 99%
“…Even though the results showed that the iPhone method achieved higher knowledge results than the traditional classroom lesson, no statistically significant differences were found between the iPhone and the classroom lesson. Chuang et al (Chuang et al, 2014) studied how happiness can improve learning performance by using interactive systems. The proposed system was a somatosensory system, which is a system that is made up of a number of different receptors like thermoreceptors, photoreceptors, mechanoreceptors, or chemoreceptors like the human body.…”
Section: Related Workmentioning
confidence: 99%
“…Past studies showed that digital games with more motion‐sensitive interactions had a positive influence on participants' learning, helping them improve their learning performance (Chuang et al, 2014; Pan, 2017). Therefore, it was possible that the digital games adopted in the course would affect students' learning, and the different movements might also influence their learning outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The results in the study demonstrate that learners in the experimental group who used the ECIRS to support their digital reading of a Q&A article had significantly better reading comprehension than those in the control group who used the MCIRS, but the difference in comprehension of a pure text article was not significant. Previous studies (Chuang et al, 2014;Hsiao and Chen, 2016) have found learning interfaces that respond naturally to human sensory organs, such as somatosensorily controlled learning games, can significantly influence learning outcomes because they enable learners to immerse themselves in the learning atmosphere, thus improving learning performance. The proposed ECIRS is very close to natural human reading by eye and so yields better reading comprehension than the (Hall et al, 2005;Kendeou and van den Broek, 2007) have found that text structure affects learners' reading comprehension and memory, and articles with well-structured or highly organized contents favour reading comprehension.…”
Section: Discussionmentioning
confidence: 99%